Phenotype of Transgenic Tobacco Plants (Nicotiana tabacum cv. Petit Havana SR-1) Expressing 1724orf13 Gene of Agrobacterium rhizogenes strain MAFF301724 - Niken Satuti Nur Handayani; Nobukazu Tanaka; Kazuo Yoshida (Indonesian Journal of Biotechnology, 2007)
Nicotiana tabacum cv. Petit Havana SR-1 transgenic plants expressing ORF13 of Agrobacterium rhizogenes strainMAFF301724 under different promoters displayed plant morphology abnormalities. They were small, with shortand variable internodes lengths; leaves were small, asymmetric, rounded, wrinkled and dark green; flowers wereshort, and irregularly shaped. This phenotype was also exhibited, similar, but not completely the same, to those ofhairy root syndrome, indicating that expression of ORF13 influences plant development.Keywords: ORF13, Agrobacterium rhizogenes strain MAFF301724, transgenic plants, morphology abnormalities